Kompetensi Membaca Pemahaman Siswa SD di Indonesia: Studi Kasus Kelas III SDI Sultan Agung - Puspitaningrum, Endah Tri; Afandi, Muhammad; Sari, Yunita (Diniyah: Jurnal Pendidikan Dasar, 2025)
This study aims to describe the reading comprehension ability of third-grade elementary school students and to identify the obstacles they face in understanding texts. The research employed a qualitative approach with a descriptive design. Data were collected through observation, oral tests, and in-depth interviews. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that students' reading comprehension ability falls into the "sufficient" category, with an average score of 66. The most mastered indicator was expressing opinions about the text content, while identifying main ideas and drawing conclusions were the weakest aspects. Obstacles included lack of focus while reading, low motivation and reading interest, and underutilized literacy facilities. This study recommends implementing more structured reading instruction strategies, strengthening school literacy culture, and fostering collaboration among teachers, parents, and institutions to build positive reading habits.Keywords: Reading comprehension, reading ability, reading difficulties, elementary